2020
DOI: 10.1016/j.heliyon.2020.e05033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of Platelet-to-White Blood Cell Ratio (PWR) and National Institute of Health Stroke Scale (NIHSS) in acute ischemic stroke

Abstract: Introduction Ischemic stroke can occur due to disruption of blood and oxygen supply to brain tissue. White blood cells and platelets play an important role in the pathogenesis of ischemic stroke. Several studies have concluded that the lower the platelet count and the higher the number of white blood cells in ischemic stroke patients will result in a more severe stroke and had worsen prognosis. Platelet and white blood cells counts can be converted into Platelet-to-White Blood Cell Ratio (PWR) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…NIHSS scores [ 21 ] were performed on the day of admission and on the first day and the fourth day of treatment. Scores are calculated based on the examination of various neurological items and categorized as mild (1–4), moderate (5–15), moderate to severe (16–20), and severe (21–24).…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NIHSS scores [ 21 ] were performed on the day of admission and on the first day and the fourth day of treatment. Scores are calculated based on the examination of various neurological items and categorized as mild (1–4), moderate (5–15), moderate to severe (16–20), and severe (21–24).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…It has been reported that flavonoids from Chrysanthemum morifolium may significantly improve the activity of antioxidases in the tissues of rats with lead poisoning, relieve lipid peroxidation, and antagonize oxidative injury of the brain, liver, and kidney [ 21 ]. However, the mechanism of chrysanthemum extract in ischemic stroke is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between PLTs and WBC has been introduced in the pathogenesis of several diseases (e.g., cerebrovascular infarction). PLTs have been shown to affect other blood cells by releasing chemokines and membrane ligands and also play as a bridge in white blood cells-PLT aggregates (LPAs) in the periphery [37]. Therefore, PWR can represent the degree of in ammation, and a signi cant association of PWR may show the prominent effect of PLT than WBC on sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…PWR has been reported to be a marker of systemic inflammatory response. Previous studies have shown that it can be used as a prognostic predictor of acute ischemic stroke and cancer (17)(18)(19)(20). This indicates that ischemic stroke patients with a lower platelet count and a higher number of WBCs will have worse prognosis.…”
Section: Introductionmentioning
confidence: 99%